TRENDS IN THE DEVELOPMENT OF PERSONNEL TRAINING IN THE AGRARIAN EDUCATION SYSTEM - Boltaev Nurali Shiramatovich (Galaxy International Interdisciplinary Research Journal, 2022)
The article focuses on the adaptation of the population to the constantly changing professional conditions of the agricultural sector, improving the quality of education through the assessment of human resources, training competitive personnel for the labor market and developing agricultural universities.